Legal and Environmental Implications of Shipwrecks under MARPOL and UNCLOS - Kadhafi, Muammar (Collaborate Engineering Daily Book Series, 2024)
This study examines global shipwreck management practices and their environmental implications through analysis of 762 significant cases from 45 maritime nations during 2000-2020. Using a mixed-method approach combining quantitative environmental impact data with qualitative assessment of response mechanisms, we investigated the effectiveness of technological solutions and international cooperation frameworks. Key findings reveal that the Asia-Pacific region accounts for the highest concentration of incidents (32.2%), with advanced technology implementation showing significant improvement in management outcomes (92% success rate for ROV surveys). Bilateral response mechanisms demonstrated superior efficiency with reduced response times (2.8 days average) and higher success rates (92%) compared to unilateral efforts. Strong correlation between technological adoption and environmental recovery rates (r=0.85, p<0.001) indicates the importance of modernizing management approaches. Analysis shows a positive trend in reducing environmental impact, with oil spill volumes decreasing from 45,200 tons in 2000 to 22,100 tons in 2020. These findings suggest the need for enhanced international cooperation, standardized technological implementation, and region-specific management strategies to improve global shipwreck response effectiveness. The study provides evidence-based recommendations for policymakers and maritime authorities to strengthen existing frameworks and adopt more efficient management practices.